Protection of intellectual property objects in institutions of general secondary education: problems at the present stage - Luniachek, V; Kravchuk, N (Problems of Engineer-Pedagogical Education, 2019)
The paper deals with topical issues of intellectual property protection in institutions of general secondary education on the basis of the analysis of their activities, with a special focus on teachers’ work within the teaching-learning process. The article analyzes scholarly works regarding the issue under investigation (especially the ones that belong to Ukrainian scientists), makes a reference to the relevant domestic normative legal acts in force and identifies the problematic aspects of the legal protection of teachers’ intellectual property. The article also analyzes materials concerning issues of intellectual property protection at the regional and school levels of education management (materials of seminars, sessions, meetings of methodological unions and conferences). The article highlights the key directions of methodological and administrative work related to the relevant issue (i.e. a system of measures aimed at informing teaching professionals about their innovative activity and the ways to protect their methodological works) and considers the groups of objects of creative work of teachers and heads of educational institutions that are protected as their innovative work. The paper proves the necessity of creating an effective system of the advanced training of teachers and managers of education in this field. Particular attention is paid to the technology transfer procedure in the system of general secondary education (both commercial and noncommercial), emphasizing the need to commercialize certain aspects of creative activity of teaching professionals. Special emphasis is put on the fact that the protection of intellectual property rights of teachers regarding their creative works will contribute to the growth of respect for them in society, which is extremely relevant in the context of the implementation of the New Ukrainian School Concept. The article highlights the stages leading to the increase of the level of teachers’ creative activity and to the establishment of conditions necessary to guarantee teachers’ intellectual property protection. The present paper also substantiates the topical issues of intellectual property protection in institutions of general secondary education and provides examples of educational institutions in Ukraine which can help inform teachers about the existing regulations in the field.